Characteristics, outcomes and the necessity of continued guideline-directed medical therapy in patients with heart failure with improved ejection fraction - Qin-Fen Chen; Yindan Lu; Christos S. Katsouras; Yangdi Peng; Junfang Sun; Mingming Li; Chenyang Liu; Hongxia Yao; Liyou Lian; Xiaofang Feng; Wei-Hong Lin; Xiao-Dong Zhou (Annals of Medicine)
Background Much remains to be learned about patients with heart failure with improved ejection fraction (HFimpEF).Objective This study sheds light on the characteristics and clinical outcomes of HFimpEF patients, including the consequences of halting guideline-directed medical therapy (GDMT).Methods This retrospective study was conducted on patients diagnosed with heart failure with reduced ejection fraction (HFrEF) who underwent a second echocardiogram at least 6 months apart between January 2009 and February 2023. The primary outcomes were major adverse cardiovascular events (MACEs), including all-cause mortality and heart failure hospitalization. The second outcome was recurrent HFrEF.Results Of 4,560 HFrEF patients were included, 3,289 (72.1%) achieved HFimpEF within a median follow-up period of 3.4 years (IQR: 1.8 − 5.9 years). Among these HFimpEF patients, recurrent HFrEF was observed in 941 (28.6%) patients during a median follow-up period of 2.3 years (IQR: 0.8–4.6 years). The proportion of patients who halted GDMT was 70.4%, 53.2%, 59.8% and 63.8% for MRA, beta-blockers, ACEI/ARB/ARNI and SGLT-2 inhibitors. Multivariable Cox analysis revealed ischemic heart disease, chronic kidney disease, coronary heart disease, lower left ventricular ejection fraction, larger left ventricular diastolic dimension and non-use GDMT are associated with recurrent HFrEF. Individuals without GDMT use exhibited lower chances of persistently recovering ejection fraction and high risks of MACEs compared to those who continue use.Conclusions HFimpEF is a common condition across all clinical follow-ups. Prevalent discontinuation of GDMT medications may contribute significantly to recurrent HFrEF, placing patients at a higher risk for poor prognosis.